PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA INTERNAL TERHADAP KINERJA PEGAWAI PENGADILAN AGAMA TINGKAT PERTAMA KABUPATEN PURBALINGGA - Mahfiroh, Yumrotun; Supriatin, Dyah; Hasibuan, Reza Rahmadi (UNPERBA, 2025)
In 2022 and 2023, the Religious Court of Purbalingga Regency still faced issues related to employee performance. This study aims to analyze the influence of work discipline, work motivation, and the internal work environment on the performance of the employees of the Religious Court of Purbalingga Regency. The type of research used is quantitative. The population of the study consists of 43 employees. The sample used in this study includes the entire population, employing quantitative methods. The results of this study indicate that work discipline has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and the internal work environment has a positive and significant effect on employee performance. Furthermore, work discipline, work motivation, and the internal work environment individually affect employee performance. The coefficient of determination is 0.493, meaning that the variables in this study influence 49% of employee performance, while the remaining 51% is influenced by other factors not examined in this study. Keywords: Work Discipline, Work Motivation, Internal Work Environment